Short term quality of life with epirubicin-fluorouracil-cyclophosphamid (FEC) and sequential epirubicin/cyclophosphamid-docetaxel (EC-DOC) chemotherapy in patients with primary breast cancer: results from the prospective multi-center randomized ADEBAR trial - Schwentner, Lukas Paul; Wischnik, Arthur (The breast, 2016)
Background - The recommendation for adjuvant dose-dense chemotherapy in high risk primary breast cancer is heterogeneous among guidelines. Understanding the impact on QoL is thereby a crucial factor, especially if the benefit is potentially low. This study aims to assess QoL as a secondary outcome in the prospective randomized multi-center ADEBAR trial. - Methods - QoL was assessed at baseline (t1), before cycle 4 FEC and cycle 5 EC-DOC (t2), 4 weeks after chemotherapy (t3) and 6 weeks after radiation (t4) using the European Organization for Research and Treatment for Cancer (EORTC) Quality of Life Core Questionnaire (QLQ-C30) and the Breast Cancer-Specific Module (QLQ-BR23). - Results - 1306 patients were enrolled into the ADEBAR trial. 675 were assigned to the FEC and 688 to the EC-DOC arm. After the beginning of treatment, global QoL dropped in both arm by 3-4 points. In the EC-DOC arm, QoL dropped further at t3 by 7 points and stayed stable in the FEC arm. 6 weeks after radiation, QoL exceeded baseline in both arms by 6-8 points. The differences between treatment arms were strongest at t3 (53.0 vs. 49.5) but did not reach clinical relevance at any point in time. Physical functioning, nausea and vomiting, fatigue and systemic therapy side effects followed with some minor exceptions similar patterns but showed higher amplitudes. - Conclusion - In conclusion, we could not detect a clinically relevant difference between the two treatment arms in global QoL, although the results consistently show that patients on EC-DOC report worse scores during the treatment.
Gesehen am 13.12.2019